The Impact of Bilateral Currency Swaps on Outward Foreign Direct Investment - Gao, Yunjie (Transactions on Economics, Business and Management Research, 2024)
The outbreak of the 2008 international financial crisis caused many countries around the world to face exchange rate fluctuations and currency crises. At the same time, China’s central bank creatively began to sign central bank currency swap agreements with other countries to stabilize exchange rates and avoid the risk of fluctuations in the US dollar. This article is based on panel data from 90 countries from 2000 to 2021, and uses empirical analysis methods to explore the impact of currency swap agreements on China’s outward foreign direct investment. On this basis, the intermediary effect is applied to analyze the financial market mechanism of currency swap policy. Research has found that currency swap agreements have a significant positive impact on the scale of China’s outward foreign direct investment (OFDI). Financing constraints are an important influencing mechanism for currency swap agreements to promote China’s OFDI. In the context of economic globalization and complex international situations, this study has important reference value for China to further promote deepening cooperation in the financial field between countries and promote the internationalization of the renminbi to facilitate the domestic and international dual circulation.